(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Natural products are being used towards pathogenic microbes since the discovery of penicillin. However, there has been increase in the frequency of microbes that are multi-antibiotic resistant which demonstrates that novel antibiotics are now much needed. Antibiotic resistance acts by changing the target of antibiotics, by increasing the efflux of antibiotic & by degrading the antibiotic itself. In this regard, this paper has attempted to evaluate the antimicrobial property of the avocado oil. Firstly, the oil was obtained commercially and the paper discs were laced with increasing amounts of it & then kept on a lawn culture of Candida albicans & Saccharomyces cerevisiae. The results were observed for 24 hours &Cyclohexamide was taken as positive control. After 24 hours, Cyclohexamide showed highest zone of inhibition while the increasing amount of the oil also showed good inhibition. This thereby opens up the possibility of procuring anti-fungals or even antibiotics from this oil commercially.